Survey of the nutritional recommendations and management practices adopted by feedlot cattle nutritionists in Brazil - Oliveira, C. A. [UNESP]; Millen, D. D. [UNESP] (Elsevier B.V., 2014)
Thirty-three feedlot cattle nutritionists were surveyed to evaluate the management practices and nutritional recommendations adopted by feedlots in Brazil. The web-based survey consisted of 81 questions that included: general information (n = 10); general commodity information (n = 15); use of coproducts (n = 5), roughage source and level (n = 5); adaptation methods (n = 7); feed mixers (n = 6); feeding management (n = 6); cattle management and type of cattle fed (n = 13); formulation practices (n = 9); information resources used for nutritional recommendations (n = 2); and additional questions (n = 3). In total, the 33 nutritionists were responsible for approximately 2,658,000 animals, and moreover, 65.5% of those participants had clients that feed less than 5000 animals yearly. Corn was the primary source of grain used in feedlot diets (87.9%) and cracking was the primary processing method recommended by nutritionists (57.6%). The average concentrate and roughage inclusion in finishing diets was 79.0% and 21.0%, respectively. The main challenges faced by nutritionists are the lack of available and precise equipment and lack of trained employees with respiratory diseases as the main health problem. This survey of nutrition and management practices should aid in the development of research for the feedlot industry in Brazil and similar tropical climates, as well as provide data to facilitate the broader application of future NRC models. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: Adaptation; Distribution; Forages; Grains; Ionophores